LOS SERVICIOS COOPERATIVOS FINANCIEROS: HACIA UNA INCLUSIÓN EN EL MERCADO MEXICANO DE AHORRO Y PRÉSTAMO - Louvier, Juan Manuel Martínez; Jiménez, Rafael Espinoza (European Scientific Journal, ESJ, 2013)
﻿Mexican economic system has been changing throughout the last decades resulting in a social inequity growth. Within the financial spectrum of savings and credit, the exclusion phenomena appears with underlined differences between the commercial banking services and the cooperative financial institutions. This article shows the financial services present picture, focusing on the respective cycles and, especially on the marked asymmetries on coverage ratio and management resources efficiency. Finally, it is proposed the boost of cooperative entities as a privileged manner to reduce finance exclusion.